Longitudinal assessment of the quality of life and patterns of antidiabetic medication use in patients with type 2 diabetes, Saudi Arabia perspective, DISCOVER study. (2nd January 2023) - Al-Rubeaan, Khalid; Banah, Faisal; Alruwaily, Fayez G.; Sheshah, Eman; Alnaqeb, Dhekra; AlQahtani, Awad M.; Ewais, Diaa; Al Juhani, Nassr; Hassan, Abdul-Hameed; Youssef, Amira M.
Abstract: Objectives: Patients with type 2 diabetes nowadays have a wide range of new antidiabetic medications with better efficacy and safety. Physicians' attitude toward selecting antidiabetic medications to reach targeted glycemic control and better quality of life (QOL) has not been studied prospectively. The global DISCOVER study aims to comprehensively provide a real-world assessment of the treatment pattern changes for patients with type 2 diabetes, in addition to QOL assessment. The Kingdom of Saudi Arabia was one of the countries participating in the DISCOVER study program. Methods: This study is a part of the prospective, longitudinal multinational DISCOVER study conducted in 38 countries including Saudi Arabia, a country facing an epidemic of type 2 diabetes, recruited 519 adult patients with type 2 diabetes with a mean age of 52.4 ± 11 years, where, they were followed up for three years period, where 477 patients completed the follow-up period. The clinical, biochemical, and patient lifestyle data were assessed periodically during the study period. DISCOVER study is registered with ClinicalTrials.gov identifiers: NCT02322762. Results: The most frequently used antidiabetic medications (ADMs) initially and during the follow-up were biguanides (metformin) and sulfonylureas (gliclazide, glibenclamide, glimepiride, glipizide, and glyclopyramide). Insulin (premix Insulin, basal insulin, and basal/bolus insulin) and dipeptidyl peptidase-4 (DPP-4) inhibitors (sitagliptin, vildagliptin, saxagliptin, and linagliptin) were the most frequent second and alternative of therapy. Other medications namely thiazolidinediones (TZds) (pioglitazone and rosiglitazone), incretins (exenatide and liraglutide), and Sodium-glucose co-transporter-2 (SGLT-2) inhibitors (canagliflozin) were used at a lesser rate. Drug availability, efficacy, and safety were the main determinants for choosing antidiabetic medications. The physical component score of the QOL had shown a significant decrease, while the mental component score has demonstrated an increase in QOL using SF36v2 Survey. Conclusions: There is an increasing trend of using of newly available ADMs, mainly DPP-4 inhibitors. The major limitation of ADMs use is related to efficacy, availability, and safety. This warrant taking all the measures to overcome these limitations through adopting a multidisciplinary team approach for close monitoring of the patients and any unfavorable side effects. Additionally, global insurance coverage for all patients with type 2 diabetes could be a solution for the drug availability factor.